Penerapan Multi-Attribute Utility Theory (MAUT) Dalam Penentuan Pegawai Terbaik - Nuroji Nuroji (PT. SNN MEDIA TECH PRESS, 2022)
The best employee selection information system is an information system used by an organization or company to support the selection process and selection of the best employees or employees. This study aims to select the best employees using criteria of Ability, Discipline, Performance, and Responsibility by applying the multi-attribute utility theory (MAUT) method as a consideration for decision making. The calculation results of the MAUT method resulted in the best employee recommendation obtained on behalf of Handoko with a value of 0.7705 getting rank 1. 2nd place was obtained by Yessi with a value of 0.502, 3rd place was obtained by Galuh with a value of 0.2512, 4th place was obtained by Jenni with a value of 0.1991, and 5th place was obtained by Wahyu with a value of 0.1742.